Normal Standards for Uric Acid, Blood Sugar, Blood Pressure, Body Mass Index as a Step to Control the Risk of Non-Communicable Diseases (NCDs) in the Kumelembuai Dua Village Community in South Minahasa Regency, North Sulawesi Province - Agus Rokot; Marlyn M. Pandean; Agnes T. Watung; Yozua T. Kawatu (Al Makki Publisher, 2025)
Non-communicable diseases (NCDs) are often considered trivial and can trap humans due to ignorance within normal limits: uric acid, blood sugar, blood pressure, and body mass index, which can lead to disease. Abnormal conditions can trigger NCDs gradually but surely. These conditions, if not anticipated through symptom observation and control of normal levels, can cause death. The causes are diverse, including genetic factors and environmental influences such as diet, sleep, activity, and social environment. Data from Kumelembuai Village, South Minahasa Regency, North Sulawesi, shows that this research uses qualitative methods, following Basrowi & Suwandi (2014). Blood samples were taken in February-March 2025 to determine normal standards for uric acid, blood sugar, and BMI in adult men and women, mainly housewives, with a total of 72 respondents. The results show that women’s average uric acid level is 9.12 mg/dL, men’s 9.4 mg/dL; blood sugar averages are 98.02 mg/dL for women and 115.94 mg/dL for men; blood pressure averages are 135.34/79.21 mmHg for women and 151.56/80.25 mmHg for men; BMI averages are 26.46 for women and 24.75 for men. Overall, some values exceed normal thresholds, indicating a risk of NCDs. The conclusion is that these levels surpass standard normal limits and could lead to health issues. Early steps are necessary to prevent NCDs by paying attention to factors such as genetics, environmental influences, and lifestyle patterns, including eating, sleeping, activity, and social gatherings that may trigger the consumption of foods increasing disease risk.